PP42 A mixed methods evaluation of a local-level alcohol availability intervention: "reducing the strength". (31st August 2015) - Egan, M; Pliakas, T
Abstract : Background: Reducing the local availability of alcohol may reduce alcohol-related harms. In the UK, local authorities are becoming increasingly interested in an intervention called 'Reducing the Strength' (RtS) whereby off-licence shops and supermarkets voluntarily stop selling inexpensive super strength (≥6.5% alcohol by volume) beers and ciders. We conducted a mixed methods evaluation to describe, measure and understand the effects of this example of local policy innovation. Methods: The qualitative phase involved documentary analysis and interviews with public health, police, licensing and retail professionals (n = 15) to gain multi-sectoral perspectives of the intervention, its aims, implementation and perceived impacts. The quantitative phase involved difference-in-differences analysis of data from a large retail chain: data on unit alcohol sales were obtained for three UK counties (131 stores). In one county the intervention started 12 months earlier than the others, allowing for a pre–post study design with a delayed implementation comparator. Results: Qualitative findings highlighted multiple perspectives from different stakeholders. Those responsible for intervention development emphasised the need to link it with support services and policing strategies. Street drinkers were the initial target for the intervention, but public health practitioners suggested mechanisms for broader population impacts through reduced purchasing and consumption of alcohol units. Our retail analysis found that during the baseline/pre-intervention period, the intervention and comparison areas sold, on average, 170393 and 183296 alcohol units per store (respectively), and 174703 and 201453 units at follow up. Therefore both intervention and comparison areas experienced increased sales at follow-up, with the difference between the two areas widening from 12903 to 26750 (p = 0.690). Conclusion: Findings from our quantitative analysis were inconclusive. The implementation did demonstrate the feasibility of co-opting retailer and public sectors into strategies that linked community safety, store security and public health goals.